Da doutrina do interesse bem compreendido n'A Democracia na América - Roberta K. Soromenho Nicolete (Araucaria, 2019)
According to Alexis de Tocqueville, in the state of equality of conditions liberty is under serious threat. The passion for equality, which is the first and most intense passion of a democratic people, may prompt them to exchange liberty for despotism, in so far as they are willing to surrender themselves entirely to the search of material goods and self-interest, and to resign their power of judgment for the sake of the opinion of the majority, which is the real source of authority in such a social state. Taking this fragile balance between liberty and equality into account, this paper aims the consideration of American customs which allows Tocqueville to postulate a social theory (not a description of this society), the doctrine of interest properly understood, which may link analytically virtue and interest and instruct democratic societies.